2021
DOI: 10.4037/ajcc2021108
|View full text |Cite
|
Sign up to set email alerts
|

Implementing AACN’s Healthy Work Environment Framework in an Intensive Care Unit

Abstract: Background Bedside nurse turnover in the United States is 15.9%, representing a national challenge that has been attributed to poor work environments. Healthy work environments are associated with improved nurse satisfaction and retention as well as positive patient outcomes; unhealthy work environments have the opposite effects. Objectives To implement the American Association of Critical-Care Nurses (AACN) healthy work envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Second, hospitals with a better working environment, even in times of pandemic, have better results for the risk of burnout and intention-to-leave the job and profession than hospitals with a worse environment. This association has already been demonstrated in other studies and it seems that hospitals with a better work environment are better able to protect the wellbeing of nurses even in times of high stress (Alharbi et al, 2020;Kester et al, 2021;Lake et al, 2022;Sermeus et al, 2011;Van den Heede et al, 2019;Wei et al, 2018).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 52%
See 1 more Smart Citation
“…Second, hospitals with a better working environment, even in times of pandemic, have better results for the risk of burnout and intention-to-leave the job and profession than hospitals with a worse environment. This association has already been demonstrated in other studies and it seems that hospitals with a better work environment are better able to protect the wellbeing of nurses even in times of high stress (Alharbi et al, 2020;Kester et al, 2021;Lake et al, 2022;Sermeus et al, 2011;Van den Heede et al, 2019;Wei et al, 2018).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 52%
“…There is a large body of evidence that shows that nurse workload, the quality of the work environment, and patient care demands influence patient outcomes (Cho et al, 2015;Lake et al, 2020;Simonetti et al, 2021). A study in the United States (US) found that interventions that aim to provide better work environment standards (e.g., true collaboration, authentic leadership, collaboration, effective decision making, appropriate staffing, meaningful recognition) are associated with improved employee satisfaction, turnover, and average job tenure among ICU nurses (Kester et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This is based on the intention of nurses to stay in their current position, nurses remaining in the profession postpandemic, and the need for authentic leadership. 23,24 This study contributes to the evolving body of nursing knowledge. It has provided a more detailed understanding of the health of the work environment and perceptions of new nurses during the transition to practice.…”
Section: Discussionmentioning
confidence: 92%
“…Staffing has been identified as one of health care's most important and complex issues. 22,23 Although some immediate opportunities are within the frontline manager's control, staffing is a broader issue that must be addressed nationally. The National Staffing Think Tank is 1 broad-scale initiative that is working to identify priorities and practical strategies to inform the focus of future initiatives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation